Identification of Molluscan Animal Image in Two-Dimensional Print Media - Nova Mujiono; Alfiah Alfiah; Riena Prihandini; Pramono Hery Santoso (Jurnal Moluska Indonesia, 2021)
Humans have known mollusks for a long time. The diverse and unique shell shapes are interesting to draw. The easiest medium to describe the shape of a mollusk is in two dimensions. This study aims to identify various images of mollusks in two-dimensional print media such as cloth, paper and plates. Based on the 10 sources of photos analyzed, 56 species of mollusks from 38 families were identified. The Gastropod class dominates with 45 species from 31 families, followed by Bivalves with 7 species from 5 families, then Cephalopods with 4 species from 2 families. Some of the problems found are the shape and proportion of images that different with specimens, some inverted or cropped images, different direction of rotation of the shells with specimens, and different colour patterns with specimens. Biological and distributional aspects of several families will be discussed briefly in this paper.